Enteric Access: IR Perspective - Lim, Marc Michael Del Rosario (Digestive Disease Interventions, 2023)
Gastrostomy tube placement may be needed for nutritional support, as in the setting of neurogenic dysphagia or head and neck malignancy, or for gastric decompression, as in the setting of malignant small bowel obstruction. Additionally, gastrojejunostomy or direct jejunostomy tubes may be needed in the setting of gastric outlet obstruction among other indications. Surgical, endoscopic, and percutaneous approaches are all well-described with generally similar outcomes. In this article, the standard radiologic percutaneous gastrostomy technique is reviewed including both the “push” and “pull” methods. Then, the special indications and techniques of advanced percutaneous enteral access such as percutaneous transesophageal gastrostomy and direct jejunostomy are discussed with examples shown.
Keywords: gastrostomy; jejunostomy; advanced technique